Estrous Cycle Response in Mice (Mus musculus) with CSE (Crude Sperm Extract) Injected Intraperitoneally - Mutiati, Enni; Rahayu, Sri; Ciptadi, Gatot; Nasich, Moch. (Graduate School, Universitas Brawijaya, 2016)
Sperm protein has an important role in fertilization process. It becomes antigenic when it is injected to body and can increase TNF-α secretion. TNF-α in blood vesssel can inhibit estradiol synthesis. Estradiol has a significant role in repduction cycle, especially in estrous cycle. The study aims to understand the influence of Crude Sperm Extract (CSE) to mice (Mus musculus) estrous cycle. 16 fertile mices strain Balb-C aged 3-4 months, weighed 20-30 g was divided into 4 groups. P0 is a control group injected by PBS, group P1, P2, and P3 injected by CSE with 1.5 mg.ml-1, 2 mg.ml-1, and 2.5 mg.ml-1. CSE is injected intraperitoneally during mice's diestrus phase. CSE is injected in day 0, day 12, day 24 and observed daily. The data are descriptively analyzed. The results show that CSE with molecule weight between 26.8-176.8 kDa influences estrous cycle. Keywords: Crude Sperm Extract, estrous cycle, folliculogenesis, Mus musculus